Simultaneous Improvement of the Long‐Term and Thermal Stability of the Perovskite Solar Cells Using 2, 3, 4, 5, 6‐Pentafluorobenzoyl Chloride (PFBC)‐Capped ZnO Nanoparticles Buffer Layer. Issue 10 (6th August 2020) - Ismail, Irfan; Wei, Junfeng; Sun, Xue; Zha, Wusong; Khalil, Maria; Zhang, Lianping; Huang, Rong; Chen, Zhenjie; Shen, Yanbin; Li, Fangsen; Luo, Qun; Ma, Chang-Qi
Abstract : Stability is a big issue for the commercialization of perovskite solar cells. The degradation of perovskite solar cells is a complex physical–chemical process related to the photoactive layer, the interface layer, and the metal electrode. Zinc oxide (ZnO) is a popular material used as the electron‐transporting layer (ETL) in perovskite solar cells. A major problem of the ZnO ETL for perovskite solar cells is the thermal instability caused by the chemical reaction between ZnO and perovskite layer. Aiming to solve the degradation issue of perovskite solar cells a kind of ZnO nanoparticle that is chemically tailored with 2, 3, 4, 5, 6‐pentafluorobenzoyl chloride (ZnO@PFBC) is provided. Herein, the migration of halogen and zinc that takes responsibility for the thermal degradation of the p–i–n‐type perovskite solar cells through time of flight secondary‐ion mass spectrometry (ToF–SIMS) and X‐ray photoelectron spectroscopy (XPS) results is proved. Using ZnO@PFBC as a modifier of PC61 BM, both the ion migration and the chemical reaction of ZnO and perovskite are suppressed. The thermal stability and long‐term illumination stability both in N2 and in ambient conditions are simultaneously improved, 75% of the initial efficiency remaining after 200 h of annealing at 85 °C. Abstract : The thermal stability and long‐term illumination stability both in N2 and in the ambient condition of the perovskite solar cells are simultaneously improved using a 2, 3, 4, 5, 6‐pentafluorobenzoyl chloride‐capped ZnO as a modifier of PCBM electron‐transporting layer (ETL).